Factor structure of problem-solving efficacy among college Algebra students - Anoling Jr., Oscar C.; Dagdag, Januard D.; Pascual, Jefferson F.; Salviejo, Ryan P. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This paper discusses the development of the Problem – Solving Efficacy Scale on College Algebra. Through factor analytic research design, the scale underwent five development stages including assessment of factorability of the data, factor extraction, factor rotation and interpretation, rotation confirmation, and internal consistency analysis. In the 80 – item questionnaire administered to 80 randomly selected College Algebra students of Isabela State University, structural validity was attained with 34 scale items grouped into four components; namely, physiological/somatic responses, social persuasions, vicarious experiences, and mastery experiences. The developed instrument can explain 55.36% of the overall variance and has a high reliability coefficient ( .87), confirming that the four factors are integral to problem-solving efficacy in College Algebra. Physiological/Somatic responses and social persuasion explain greater amount of variance than mastery experience and vicarious which suggests that while teachers give importance on improving students’ mastery level and modelling them with successful others in problem-solving activities in College Algebra, they should also encourage students to like the subject and see themselves successful in it, and provide them with sincere and timely encouragements especially problem-solving is a challenging learning tasks. College Algebra teachers should then design attainable learning goals coupled with challenging teaching-learning activities and constructively aligned assessment, and de-emphasize drills, speed tests, and competitions in problem-solving lessons.